Aspergilloma in a young patient with autosomal-dominant hyper-IgE syndrome - Ismail, Intan Hakimah; Zainal Abidin, Mohd Azri; Mohamed Nashrudin, Khairoon Nisa (Asia Pacific Association of Allergy, Asthma, and Clinical Immunology, 2024)
Signal transducer and activator of transcription 3 (STAT3) deficiency is the primary cause of autosomal dominant hyper IgE syndrome (AD-HIES), also known as Job syndrome. Approximately 90% of affected individuals experience bacterial pneumonia, with about 67% developing pulmonary complications such as bronchiectasis or pneumatoceles. Moreover, STAT3 deficiency significantly predisposes patients to fungal infections, particularly aspergillosis. Aspergilloma, often referred to as a mycetoma or fungal ball, is the most frequent pulmonary manifestation of Aspergillus species, typically forming within preexisting lung cavities. Diagnosis relies on a combination of radiographic findings and serological or microbiological evidence of Aspergillus involvement.